The Other Green Jobs: Legal Marijuana and the Promise of Consumption-Driven Economic Development. (March 2019) - Doussard, Marc
Legalizing marijuana at the state level establishes via fiat a new industry. In practice, legal marijuana constitutes a large-scale test of consumption-driven economic development policies, which seek to shape industry and job growth via changes in local spending. Drawing on the critical case of Colorado, I assess the economic development outcomes and future potential of legal marijuana, and evaluate the broader applicability of consumption-driven development processes heretofore confined to the arts and isolated local cases. While most states should be able to replicate Colorado's import-substitution gains, the most enduring economic benefits to legalization require place amenities that legalization alone cannot provide.